ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA HOTEL GRAND TEMBAGA DI KOTA TIMIKA - Dessy Sere; Rulan L Manduapessy (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the quality of service at the Grand Copper Hotel and to determine the effect of service quality on customer loyalty at the Grand Copper Hotel. To achieve this goal, this study uses associative research methods. The required data were collected using interview techniques, observation, distribution of research questionnaires and documentation. To analyze the research data, a simple linear regression analysis was used. The results showed that service quality has a significant effect on customer loyalty at the Grand Copper Hotel in Timika City